TEACHING READING BY COMBINING KWL STRATEGY WITH 3-2-1 STRATEGY AT JUNIOR HIGH SCHOLL - Srihwahyuni, Dian; M.Pd, Imron Hadi (Pendidikan Bahasa Inggris, 2014)
AbstractThis paper is talking about teaching reading by combining KWL strategy with 3-2-1 strategy at junior high school which is aimed at discussing how to teach reading by combining the two strategies. There are three stages of these strategies in teaching reading. Those are pre-speaking, while-speaking, and post-speaking in which divided in the following steps; the teacher prepares the column in the form of KWL or 3-2-1. The teacher selects an article or a passage from the students textbook. Then, He/she asks the students to record (at least)three things what they know or what they have heard about the topic in the column K. Next, He/she asks the students to write (at least) two things what they want to learn from the text in the column W. After reading the text, he/she asks the students to write (at least) one question what the students learned from the text in the column L. To see the studentsâ achievement of reading comprehension, the teacher can prepare some questions. If the students achievement of reading still low, the two strategies can be repeatedÂ  in the same steps of the combining strategies.